Keefektifan Konseling Kelompok Cognitive Behavior Teknik Cognitive Restructuring untuk Mereduksi Perilaku Self Harm pada Siswa SMPN 1 Rajadesa - Khoerotunnisa Aprilia; Akhmad Fajar Prasetya (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
The phenomenon underlying this research indicates an increase in self-harming behavior among junior high school students. This study aims to reduce such behavior through group counseling using cognitive behavioral techniques, specifically cognitive restructuring. The research method employed is a pre-experimental design with a one-group pretest-posttest. The results show a decrease in self-harm behavior scores among the students. This is supported by the paired sample t-test statistical analysis, which indicates a significance value (2-tailed) of 0.000, meaning it is less than 0.05. Therefore, it can be concluded that group counseling using cognitive behavioral techniques, particularly cognitive restructuring, is effective in reducing self-harm behavior among students at SMP Negeri 1 Rajadesa. The behavioral changes observed in students after participating in this counseling include a decrease in the frequency of self-harm, improved emotional stability, enhanced coping skills, increased self-awareness, and greater social involvement.